Severity of gambling is associated with severity of depressive symptoms in pathological gamblers. - Rømer Thomsen, K; Callesen, M; Linnet, J; Kringelbach, M; Møller, A (2009)
The objective of this study was to investigate the relationship between gambling severity and depressive symptoms in pathological gamblers addicted to slot machines, with the hypothesis that comorbid depressive symptoms are associated with exacerbated gambling symptoms and behavior. Twenty controls and 20 pathological gamblers with different levels of depressive symptoms were studied during slot machine gambling. We found exacerbated gambling behavior in gamblers with high compared to low levels of depressive symptoms in terms of self-reported gambling urge (P < 0.01) and excitement from gambling (P < 0.05), number of games played (P < 0.01), and duration of gambling (P < 0.05). A correlation between depressive and gambling symptoms was found (r = 0.602, P < 0.01), thereby questioning which symptoms contribute to the exacerbated gambling behavior. Regression analyses showed that the symptoms influenced gambling behavior albeit in different ways. Although gambling symptoms predicted the rate of games played (P < 0.001), depressive symptoms predicted gambling urge (P < 0.01) and duration of gambling (P < 0.05). We discuss whether gambling symptoms only co-occur with other disorders; the need to look beyond the classification of pathological gambling as an impulse control disorder; and the potential role of anhedonia in depressed gamblers.